The effectiveness of advertising campaign towards organ donation and transplant in Malaysia / Muhammad Aidzul Idham Keroman - Keroman, Muhammad Aidzul Idham (2013)
Organ donation and transplant is the process of donating a person’s organs and tissues to be transplanted to someone else, in many cases, such as very ill or dying. Organ transplant (or transplantation) is a medical procedure for treatment of patients with organ failure to function. It is already prove medically to save lives and improves the quality of life. The aim of this study is to look how the perceptions and misunderstandings affect the awareness towards organ donation.